Neural predictors of alcohol use and psychopathology symptoms in adolescents - BRUMBACK, TY (Dev Psychopathol, 2016)
Adolescence is a period marked by increases in risk taking, sensation seeking, and emotion dysregulation. Neurobiological models of adolescent development propose that lagging development in brain regions associated with affect and behavior control compared to regions associated with reward and emotion processing may underlie these behavioral manifestations. Cross-sectional studies have identified several functional brain networks that may contribute to risk for substance use and psychopathology in adolescents. Determining brain structure measures that prospectively predict substance use and psychopathology could refine our understanding of the mechanisms that contribute to these problems, and lead to improved prevention efforts. Participants (N = 265) were healthy substance-naïve adolescents (ages 12–14) who underwent magnetic resonance imaging and then were followed annually for up to 13 years. Cortical thickness and surface area measures for three prefrontal regions (dorsolateral prefrontal cortex, inferior frontal gyrus, and orbitofrontal cortex) and three cortical regions from identified functional networks (anterior cingulate cortex, insular cortex, and parietal cortex) were used to predict subsequent binge drinking, externalizing symptoms, and internalizing symptoms. Thinner dorsolateral prefrontal cortex and inferior frontal cortex in early adolescence predicted more binge drinking and externalizing symptoms, respectively, in late adolescence (ps < .05). Having a family history of alcohol use disorder predicted more subsequent binge drinking and externalizing symptoms. Thinner parietal cortex, but not family history, predicted more subsequent internalizing symptoms (p < .05). This study emphasizes the temporal association between maturation of the salience, inhibition, and executive control networks in early adolescence and late adolescent behavior outcomes. Our findings indicate that developmental variations in these brain regions predate behavioral outcomes of substance use and psychopathology, and may therefore serve as prospective biomarkers of vulnerability.